Determination of Crack Resistance of the Cover and Slide Glass by Indentation Method with the Visualization Using Atomic Force Microscopy - V. A. Lapitskaya; T. A. Kuznetsova; S. A. Chizhik (Приборы и методы измерений)
Crack resistance of two types of glass was studied – cover glass (0.17 mm thick) and slide glass (2 mm thick) using an improved technique through the use of the probe methods, which makes it possible to increase the accuracy of determining the crack resistance of glass. Colorless silicate glass was used. Crack resistance was determined by the Vickers pyramid indentation method. Microstructure of glasses surface and deformation region after indentation were studied using an atomic force microscope. Mechanical properties of glasses were determined by nanoindentation. Surface relief of a glass slide is rougher than that one of a cover glass. Roughness Rz for a cover glass is less than for a slide glass. Specific surface energy value of 0.26 N/m is higher for the slide glass compared to the coverslip. One elastic modulus value E of the cover glass is 48 GPa, and that one of the slide glass is 58 GPa. The microhardness value H is almost the same for by the glasses and amounts to 6.7 GPa for a slide glass and 6.4 GPa for a cover glass. Atomic force microscope images of deformation region after indentation with a Vickers pyramid show that the first cracks appear at a load of 1 N on the slide glass, and at 2 N on the cover glass. At a load of 3 N, the cover glass is destroyed. Based on the results of crack resistance calculations it was found that critical stress intensity coefficient KIC values are 1.42 MPa∙m1/2 for a glass slide, and 1.10 MPa∙m1/2 for a cover glass.